Cervical spondylotic myelopathy associated with syringomyelia: A case report - (:unkn) unknown (Springer Paris, 2000)
A case of syringomyelia associated with cervical spondylotic myelopathy is presented. A decompressive cervical laminectomy was performed. The patient improved gradually after operation. It is concluded that the choice of surgical treatment in cases with syringomyelia associated with cervical spondylotic myelopathy requires a careful neurological and radiological examination based on the findings of magnetic resonance imaging (MRI) and cine-MRI.
Keywords: Cervical spondylotic myelopathy; MRI; Syringomyelia